1969
DOI: 10.12669/pjms.314.7303
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of uterine rupture at university teaching hospital Pakistan

Abstract: Objective:To determine the risk factors, management modalities, fetomaternal outcome of uterine rupture cases at University teaching hospital in Pakistan.Methods:This retrospective descriptive study was conducted at the Department of Gynaecology and Obstetrics Liaquat University of Medical and Health Sciences (LUMHS) for a period of one year from January 1st to December 31st 2012. Main outcome measures were frequency, age, parity, booking status, risk factors, management modalities, fetal and maternal mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

1975
1975
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 11 publications
3
12
0
Order By: Relevance
“…But this remaining incidence 1.14% is still very high in comparison to other countries as 0.02% in UK (Fitzpatrick et al), 0.0521% in China (Xiaoxia B et al), 0.67% in Pakistan (Nousheen et al), 0.85% in northern Nigeria (Akaba GO et al), 0.225% in Tanzania (Kidanto HL et al), 1.46% in southern Nigeria (Kelechi et al) and even other parts of India also as 0.07% in Mumbai (Nagarkatti RS et al). [7][8][9][10][11][12] We have observed that rupture uterus occurred much more frequently in unscarred uterus in our study group even after implementation of JSY. This might be due to deliveries conducted by untrained personnel in rural sectors where either proper medical care is still not available or the ill-informed, uneducated patient and family are still reluctant to seek any trained help.…”
Section: Anand Rs Et Al Int J Reprod Contracept Obstet Gynecol 2016mentioning
confidence: 89%
See 2 more Smart Citations
“…But this remaining incidence 1.14% is still very high in comparison to other countries as 0.02% in UK (Fitzpatrick et al), 0.0521% in China (Xiaoxia B et al), 0.67% in Pakistan (Nousheen et al), 0.85% in northern Nigeria (Akaba GO et al), 0.225% in Tanzania (Kidanto HL et al), 1.46% in southern Nigeria (Kelechi et al) and even other parts of India also as 0.07% in Mumbai (Nagarkatti RS et al). [7][8][9][10][11][12] We have observed that rupture uterus occurred much more frequently in unscarred uterus in our study group even after implementation of JSY. This might be due to deliveries conducted by untrained personnel in rural sectors where either proper medical care is still not available or the ill-informed, uneducated patient and family are still reluctant to seek any trained help.…”
Section: Anand Rs Et Al Int J Reprod Contracept Obstet Gynecol 2016mentioning
confidence: 89%
“…But the remaining maternal mortality (4.88%) is still higher in comparison to the studies like Xiaoxia B et al (0%), Fitzpatrick et al (1.3%) and lower to studies Akaba et al (14.7%), Nousheen et al (8.19%), Hussain L et al (6.6%). [7][8][9][10] We have observed that perinatal mortality was almost same in both groups i.e 93.93% and 95.12% in group 1 and group 2 respectively. This incidence of fetal case fatality rate is comparable to Akaba et al (90.7%), Kidanto H. L. et al (96.3%) and Nousheen et al (83.6%).…”
Section: Anand Rs Et Al Int J Reprod Contracept Obstet Gynecol 2016mentioning
confidence: 99%
See 1 more Smart Citation
“…5% -10% of maternal mortality is because of uterine rupture in developing countries (1). 80% -90% of fetuses in these cases could not be survived (2).…”
Section: Introductionmentioning
confidence: 99%
“…Inadequate antenatal care is a root cause for high incidence of rupture uterus in developing countries. Incidence of uterine rupture is 1:200 to 1: 3000 deliveries (1,3,4) according to level of antenatal care. Rupture of entire uterine wall and direct connection between peritoneal space and uterine cavity is defined as complete rupture.…”
Section: Introductionmentioning
confidence: 99%